2022
DOI: 10.3390/photonics9070441
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Doppler Effect in Vortex Light and Its Applications for Detection of the Rotational Motion

Abstract: The linear Doppler effect has been widely used to detect the translational motion of objects. However, it suffers difficulties in measuring the angular motion of a rotating target. In recent years, the rotational Doppler effect based on a vortex beam has been helpful to solve the problem of rotational measurement and has attracted extensive attention in remote sensing. This paper expounds the theoretical and experimental basis of the rotational Doppler effect and briefly summarizes its development for the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…It simultaneously estimates amplitude and phase errors in the range frequency domain based on dominant point targets selected in the preliminarily focused image. Reference [16] proposes the use of the linear Doppler effect to detect the translational motion of objects and provides a detailed description of the properties and analysis methods of rotational Doppler shift when the vortex beams are misaligned with the rotation axis.…”
Section: Related Workmentioning
confidence: 99%
“…It simultaneously estimates amplitude and phase errors in the range frequency domain based on dominant point targets selected in the preliminarily focused image. Reference [16] proposes the use of the linear Doppler effect to detect the translational motion of objects and provides a detailed description of the properties and analysis methods of rotational Doppler shift when the vortex beams are misaligned with the rotation axis.…”
Section: Related Workmentioning
confidence: 99%
“…[85,86] Actually, as the authors have shown, it is only a matter of modal decomposition of the incident beam into a LG beam basis attached to the rotating object. [38,[87][88][89] Let us for example consider the case of a misalignment, where the center of the incoming beam is shifted by a distance d regarded to the rotation axis. The decomposition into a LG basis can be performed rather easily and evaluated numerically.…”
Section: Beam Axis and Rotation Axis That Don't Coincidementioning
confidence: 99%
“…The topological nature of the screw WF dislocation opens impressive possibilities for the data encoding and the information transfer [49][50][51]. The specific pattern of the transverse energy flows is responsible for another interesting phenomenon-rotational Doppler effect [52][53][54][55][56][57][58][59]. Indeed, the visible phase of the azimuthal harmonic (3) depends on the mutual angular positions of an observer and the beam with respect to the axis z (see Figure 1A).…”
Section: Screw Wavefront Dislocations Also Known As Optical Vorticesmentioning
confidence: 99%
“…As a result, when the beam (or observer) rotates with the angular velocity Ω, the visible frequency changes by Δω lΩ. This effect finds fruitful applications for the spectral analysis of light beams and the distant detection of the rotational motion of various objects [55, 58, 59], which are described in detail by recent reviews [59,60]. For this reason, we do not dwell further upon the rotational Doppler shifts but proceed to some impressive non-linear effects involving the optical singularities.…”
Section: Screw Wavefront Dislocations Also Known As Optical Vorticesmentioning
confidence: 99%